Design of Phase Shift Control For Transmit/ Receive Module of ST Radar - Ghosalkar, Samikshya Suresh; Ray, K P; Rangari, Rajesh G; Gharge, Saylee Milind (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
The paper mainly focuses on the beam forming and its analysis for planar phased- array antenna, which is being developed as part of the ST Radar. The beam steering is done electronically by controlling the phase of the T/R module in such a way that the phase difference between each module is equal and it corresponds to the steering angle. The relative phase shift of each T/R module for a specified beam position is worked out using MATLAB and implemented using 6- bit digital phase shifter. The analytical results are practically demonstrated using the STM32F4xx kit of STMicroelectronics. Theoretical values of the elemental phase for each antenna element in the array, are calculated for various positions of the beam (Î¸ & Ï†). The 6-bit phase shifter results in 5.6250 phase resolution.Â In the second part of the work, the calculation of the element phase with 6-bit digital phase shifter is discussed. The calculated values of the elemental phase are truncated to an integral multiple of 5.6250.Â